ANTIFUNGAL ACTIVITY AND PHYTOCHEMICAL PROFILE OF CHLOROFORM SOLUBLE FRACTION OF DATURA METEL FRUIT - N. Jabeen; A. Javaid; E. Ahmed (Journal of Animal and Plant Sciences, 2022)
Datura metel is a weed of family Solanaceae. In the present study, dried and powdered fruits of this medicinal plant species were extracted in methanol for two weeks. After evaporating the solvent, the remaining gummy extract was mixed in water and fractionated using n-hexane to separate the non-polar fraction. The remaining aqueous phase was partitioned with chloroform in a separating funnel. The chloroform fraction was separated and evaporated on a rotary evaporator. The gummy biomass of this fraction obtained after complete evaporation of the solvent was dissolved in dimethylsulphoxide (DMSO) and its different concentrations (3.125 to 200 mg/ml) were prepared in malt extract broth. Antifungal activity of the extract was checked against a highly destructive soil-borne phytopathogen Sclerotium rolfsii isolated from bell pepper plants suffering from collar rot disease. Results revealed that there was 35–51% reduction in biomass of S. rolfsii due to different concentrations of the chloroform fraction. Twelve compounds were identified through GC-MS analysis of this fraction. The predominant were 1-hexacosanol (15.45%), 1,2-benzenedicarboxylic acid, bis (2-methylpropyl) ester (14.15%), 1-octadecanol (12.81%), 1-octadecene (12.80%) and 1-eicosanol (8.12%), which could be responsible for antifungal activity against S. rolfsii.
Keywords: Bell pepper; Datura metel fruit; methanolic extract; natural fungicides; Sclerotium rolfii